TRIPS Intermediate Language (TIL) Manual - Smith, Aaron; Gibson, Jon; Burrill, Jim; McDonald, Robert; Burger, Doug; Keckler, Stephen W.; McKinley, Kathryn (UT-Austin, Department of Computer Science, 2006)
This document specifies the TRIPS Intermediate Language (TIL) for the TRIPS architecture, a novel, scalable, low power architecture for future technologies. TIL is a RISC-like intermediate representation for use by humans and compilers that want to write low-level TRIPS code.
Uncertainty in Artificial Intelligence 2